2019
DOI: 10.1039/c9ta10443g
|View full text |Cite
|
Sign up to set email alerts
|

Light enhanced moisture degradation of perovskite solar cell material CH3NH3PbI3

Abstract: We reveal the relationship between the light enhanced moisture degradation and the photostriction effect in MAPbI3 perovskite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 43 publications
3
35
0
Order By: Relevance
“…All samples were stored in the dark to eliminate the light degradation effect on perovskite materials, and the device performance test process was carried out in ambient air (Rh = 30 ± 5%, T = 25 °C). 99 In the long-term stability testing of PSCs, the unencapsulated PSCs in ambient air were aged at 30 ± 5% Rh at around 25 °C for 1200 h, as shown in Fig. 7a.…”
Section: Resultsmentioning
confidence: 99%
“…All samples were stored in the dark to eliminate the light degradation effect on perovskite materials, and the device performance test process was carried out in ambient air (Rh = 30 ± 5%, T = 25 °C). 99 In the long-term stability testing of PSCs, the unencapsulated PSCs in ambient air were aged at 30 ± 5% Rh at around 25 °C for 1200 h, as shown in Fig. 7a.…”
Section: Resultsmentioning
confidence: 99%
“…[ 381 ] In situ X‐ray photoelectron spectroscopy (XPS) further confirmed the escape of gaseous NH 3 , HI, and I 2 byproducts from the films, leaving behind hydrocarbonaceous species on the surface. [ 382–384 ] In addition, uniform expansion of the halide perovskite unit cell was also observed when exposed to continuous light soaking, [ 385,386 ] which sped up the moisture penetration into the bulk of the halide perovskite, followed by humidity‐induced degradation. In contrast, Bastos et al reported a 50% reduction in photocurrent and 15% reduction in both photovoltage and fill factor during the first 100 h of illumination, [ 387,388 ] even though no changes were recorded in the optical absorbance and X‐ray diffraction spectra of the sample before and after light soaking; visible light soaking deteriorates the PV performance without degradation of the halide perovskite.…”
Section: Stability: Achieving Parity With Silicon Pvmentioning
confidence: 99%
“…[ 73 ] This process can be further accelerated in the presence of external illumination, something that has been attributed to the photostriction effect observed in LHP that could favor the penetration of H 2 O molecules within the perovskite lattice. [ 74 ]…”
Section: A Perovskite Is a Perovskite And Its Circumstance: External Factors Determining The Optoelectronic Performance Of Lhp Filmsmentioning
confidence: 99%
“…[73] This process can be further accelerated in the presence of external illumination, something that has been attributed to the photostriction effect observed in LHP that could favor the penetration of H 2 O molecules within the perovskite lattice. [74] But the interaction of H 2 O and O 2 with the LHP lattice can also have beneficial effects as it has been demonstrated [71] Copyright 2018, Royal Society of Chemistry. b) Reproduced with permission.…”
Section: Interplay Between Structural Defects and The Surrounding Atm...mentioning
confidence: 99%